Guide to modern clothing - Sturm, Mary Mark. (New York, Webster Division, McGraw-Hill, 1973)
A high school clothing textbook covering basic and advanced sewing techniques as well as tailoring. Includes information on clothing care and management and projecting an image with clothing.
1962 and 1968 editions by M. M. Sturm and E. H. Grieser.
Bibliography: p. 547-549.
Keywords: Dressmaking; Clothing and dress; Beauty, Personal; Dressmaking; Clothing and dress